High-density mapping suggests cytoplasmic male sterility with two restorer genes in almond × peach progenies. (6th May 2015) - Donoso, José Manuel; Eduardo, Iban; Picañol, Roger; Batlle, Ignasi; Howad, Werner; Aranzana, María José; Arús, Pere
Abstract: Peach ( Prunus persica ) and almond ( Prunus dulcis ) are two sexually compatible species that produce fertile offspring. Almond, a highly polymorphic species, is a potential source of new genes for peach that has a strongly eroded gene pool. Here we describe the genetics of a male sterile phenotype that segregated in two almond ('Texas') × peach ('Earlygold') progenies: an F2 (T×E) and a backcross one (T1E) to the 'Earlygold' parent. High-density maps were developed using a 9k peach SNP chip and 135 simple-sequence repeats. Three highly syntenic and collinear maps were obtained: one for the F2 (T×E) and two for the backcross, T1E (for the hybrid) and E (for 'Earlygold'). A major reduction of recombination was observed in the interspecific maps (T×E and T1E) compared to the intraspecific parent (E). The E map also had extensive monomorphic genomic regions suggesting the presence of large DNA fragments identical by descent. Our data for the male sterility character were consistent with the existence of cytoplasmic male sterility, where individuals having the almond cytoplasm required the almond allele in at least one of two independent restorer genes, Rf1 and Rf2, to be fertile. The restorer genes were located in a 3.4 Mbp fragment of linkage group 2 ( Rf1 ) and 1.4 Mbp of linkage group 6 ( Rf2 ). Both fragments contained several genes coding for pentatricopeptide proteins, demonstrated to be responsible for restoring fertility in other species. The implications of these results for using almond as a source of novel variability in peach are discussed. Abstract : Horticulture Research A study sheds light on the complex interplay between different genomes within the cell when making fertile crosses of fruit tree species. Peach ( Prunus persica ) is self-fertilizing and genetically homogeneous. New traits such as disease resistance can therefore only be introduced by breeding with related species, such as the genetically variable almond ( Prunus dulcis ). Pere Arús and colleagues at the IRTA Centre de Recerca en Agrigenòmica, Barcelona, Spain, identified a peach–almond cross showing 'cytoplasmic male sterility' (CMS). In CMS, fertile pollen production is inhibited by genes in the cellular compartments known as mitochondria. Using genetic mapping, the researchers showed that the progeny of peach–almond crosses would be sterile were it not for two 'restorer' genes in the nuclear genome, which reestablish fertility. This understanding will facilitate breeding of new peach varieties using almond genes.